Natural Tourist Attraction Development Model Based On Tourism Area Cycle Of Evolution (Case Of Ponot Waterfall Attraction Asahan Regency) - Sitti Nurlaeli; Emrizal Emrizal; Femmy Indriany Dalimunthe (Nawasena: Jurnal Ilmiah Pariwisata, 2023)
The development of tourism in an area will bring many benefits to the community, namely economically, socially, and culturally. However, if the development is not prepared and managed properly, it will cause various problems that make it difficult or even detrimental to the community. The research that will be conducted aims to formulate directions for the development of the Ponot Waterfall Natural Tourist Attraction in Asahan Regency based on the Tourism Area Cycle of Evolution (TACE) model and then provide several recommendations for the development of natural tourist attractions based on the typology. This qualitative descriptive study uses four data collection techniques: observation, documentation study, focus group discussion, and literature study. This study uses research variables used to identify the natural attractions of Ponot Waterfall. The variables in the tourism components are Attraction, Accommodation, Facilities, Transportation, Infrastructure, Institutional, Promotion, Tour Packages, Ancillary Services. Then the data obtained are analyzed using the Tourism Area Cycle of Evolution (TACE), Carrying Capacity and Ansoff Matrix. Research shows that Ponot Waterfall is nature tourism that has fulfilled all the indicators in the characteristics of natural tourism areas that have not been fulfilled, namely the variable something to buy, where the natural tourism area does not yet have a distinctive product to be traded to tourists, tourism promotion and supporting facilities that have not adequate and as a tourist area, this waterfall is still managed by the community so there are still minimal facilities and development. Ponot Waterfall is in the involvement stage and its position on the Ansoff Matrix diagram is in Quadrant 1 Market Penetration: Existing Product and Existing Market. After the first and second targets have been achieved, more appropriate directions for the development of natural tourist attractions are generated based on the evolution cycle of tourist attractions